If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.08 + -0.01(x + 2) = -0.03(2 + -1x) Reorder the terms: 0.08 + -0.01(2 + x) = -0.03(2 + -1x) 0.08 + (2 * -0.01 + x * -0.01) = -0.03(2 + -1x) 0.08 + (-0.02 + -0.01x) = -0.03(2 + -1x) Combine like terms: 0.08 + -0.02 = 0.06 0.06 + -0.01x = -0.03(2 + -1x) 0.06 + -0.01x = (2 * -0.03 + -1x * -0.03) 0.06 + -0.01x = (-0.06 + 0.03x) Solving 0.06 + -0.01x = -0.06 + 0.03x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.03x' to each side of the equation. 0.06 + -0.01x + -0.03x = -0.06 + 0.03x + -0.03x Combine like terms: -0.01x + -0.03x = -0.04x 0.06 + -0.04x = -0.06 + 0.03x + -0.03x Combine like terms: 0.03x + -0.03x = 0.00 0.06 + -0.04x = -0.06 + 0.00 0.06 + -0.04x = -0.06 Add '-0.06' to each side of the equation. 0.06 + -0.06 + -0.04x = -0.06 + -0.06 Combine like terms: 0.06 + -0.06 = 0.00 0.00 + -0.04x = -0.06 + -0.06 -0.04x = -0.06 + -0.06 Combine like terms: -0.06 + -0.06 = -0.12 -0.04x = -0.12 Divide each side by '-0.04'. x = 3 Simplifying x = 3
| c^2(c^2+4c+4)-64(c^2+4c+4)= | | -2(t-1)+8t=3t-1 | | (8b+1)(8b+1)= | | 14+5(3c-2)= | | 0.40x+0.10(130)=0.20(97) | | (8m+3n)(8m-3n)= | | 0.30x+0.55(60)=0.15(128) | | 550=2*3.14*25*r+3.14*r^2 | | 2x-5/3=x+7/4 | | 6-7(x-3)=-1 | | (8b-9)(8b+9)= | | 6x+y=9 | | -3p+8=6-(9p+3) | | 24-3y+y=9 | | x^2+18x-40=0 | | 8x-5=3(2x-11) | | -7p=4 | | -7(2x+5)=26 | | (6x^4y^2+3x^2y^4)-(x^4y^2-4x^2y^4)= | | 6(x+2)=-8 | | 4+3(x+-9)=-12 | | (8x+2)-(-3x+4)= | | 3x(y+5)=25 | | 2r+3=4r-9 | | 4x+17=12x-79 | | 9x^2+100x-2965550=0 | | 1-6q=-17 | | 3e^2(2x+1)=2e^2-e^2(x+1) | | 3p+2.5=3.7 | | a^2=7a | | (12x^2)+(12y^2)+3x+2y+6=0 | | 8x-y=5 |